The link between atmospheric radicals and newly formed particles at a spruce forest site in Germany - B. Bonn; E. Bourtsoukidis; T. S. Sun; H. Bingemer; L. Rondo; U. Javed; J. Li; R. Axinte; Xin Li; Brauers, Theo; H. Sonderfeld; R. Koppmann; et al. (Atmospheric Chemistry and Physics, 2014)
It has been claimed for more than a century that atmospheric new particle formation is primarily influenced by the presence of sulfuric acid. However, the activation process of sulfuric acid related clusters into detectable particles is still an unresolved topic. In this study we focus on the PARADE campaign measurements conducted during August/September 2011 at Mt Kleiner Feldberg in central Germany. During this campaign a set of radicals, organic and inorganic compounds and oxidants and aerosol properties were measured or calculated. We compared a range of organic and inorganic nucleation theories, evaluating their ability to simulate measured particle formation rates at 3 nm in diameter (J(3)) for a variety of different conditions. Nucleation mechanisms involving only sulfuric acid tentatively captured the observed noon-time daily maximum in J(3), but displayed an increasing difference to J(3) measurements during the rest of the diurnal cycle. Including large organic radicals, i.e. organic peroxy radicals (RO2) deriving from monoterpenes and their oxidation products, in the nucleation mechanism improved the correlation between observed and simulated J(3). This supports a recently proposed empirical relationship for new particle formation that has been used in global models. However, the best match between theory and measurements for the site of interest was found for an activation process based on large organic peroxy radicals and stabilised Criegee intermediates (sCI). This novel laboratory-derived algorithm simulated the daily pattern and intensity of J(3) observed in the ambient data. In this algorithm organic derived radicals are involved in activation and growth and link the formation rate of smallest aerosol particles with OH during daytime and NO3 during night-time. Because the RO2 lifetime is controlled by HO2 and NO we conclude that peroxy radicals and NO seem to play an important role for ambient radical chemistry not only with respect to oxidation capacity but also for the activation process of new particle formation. This is supposed to have significant impact of atmospheric radical species on aerosol chemistry and should be taken into account when studying the impact of new particles in climate feedback cycles.